Modulation of cigarette smoke extract-induced human bronchial epithelial damage by eucalyptol and curcumin. (September 2021) - Reis, R; Orak, D; Yilmaz, D; Cimen, H; Sipahi, H
Smoking is one of the most important leading death cause worldwide. From a toxicological perspective, cigarette smoke serves hazards especially for the human being exposed to passive smoke. Over the last decades, the effects of natural compounds on smoking-mediated respiratory diseases such as COPD, asthma, and lung cancer have been under investigation, as well as the mechanistic aspects of disease progression. In the present study, the protective mechanism of eucalyptol (EUC), curcumin (CUR), and their combination on BEAS-2B cells were investigated in vitro to understand their impact on cell death, oxidative cell injury, and inflammatory response induced by 3R4F reference cigarette extract (CSE). According to the present findings, EUC, CUR, and their combination improved cell viability, attenuated CSE-induced apoptosis, and LC3B expression. Further, CSE-induced oxidative damage and inflammatory response in human bronchial epithelial cells were remarkably reduced by the combination treatment through modification of enzymatic antioxidant activity, GSH, MDA, and intracellular ROS levels as well as nitrite and IL-6 levels. In addition, nuclear translocation of Nrf2, a regulatory protein involved in the indirect antioxidant response, was remarkably up-regulated with the combination pre-treatment. In conclusion, EUC and CUR in combination might be a potential therapeutic against smoking-induced lung diseases through antioxidant and inflammatory pathways and results represent valuable background for future in vivo pulmonary toxicity studies.